Treating white leaf disease in sugarcane cuttings using solution plasma - Janjira Sroykaew (2018)
Sugarcane, an important agricultural crop, is susceptible to white leaf disease, which can severely damage the crop and income. The disease is caused by phytoplasma, a prokaryote in the class mollicutes. This study investigated the efficacy of treating the disease by sterilization with solution plasma technology, including wire-to-wire, plasma jet, and gliding arc systems. Nested PCR and a scanning electron microscope were used to examine the phytoplasma disease and evaluate the effectiveness of the various solution plasma treatments. The most effective treatments, in terms of balancing plant growth and disease reduction, were the wire-to-wire system, with infected specimens immersed during discharge for 2 min with discharge repeated every 2 min, for 120 min (Exp 13); and the plasma jet system, with infected specimens immersed during discharge for 30 min and then continuously immersed for 180 min (Exp 18). The wire-to-wire treatment yielded 50% disease-free sugarcane specimens with 80% growth; the plasma jet system yielded fewer disease-free sugarcane specimens (40%), but more growth (90%). Additionally, SEM results showed that the solution plasma treatments as a group reduced disease incidence by about one third compared to the controls.